Advances in the Study of the Mechanism of Gualou Xiebai Banxia Decoction in the Treatment of Coronary Heart Disease - Qiao, Xiaoyang; Zhang, Qi (Journal of Contemporary Medical Practice, 2024)
Gualou Xiebai Banxia Decoction (GXBD) is a commonly used formula for the clinical treatment of coronary heart disease, offering the advantages of wide clinical applicability and an outstanding therapeutic effect. In recent years, it has been demonstrated that Gualou Xiebai Banxia Decoction can improve the clinical symptoms of patients by correcting lipid metabolism disorders, slowing down the level of immuno-inflammation, resisting oxidative stress, improving energy metabolism, protecting endothelial cells, and promoting repair and regeneration of myocardial tissues. The objective of this paper is to present a review of the mechanism of treatment of coronary artery disease with Gualou Xiebai Banxia Decoction, with a view to providing a basis for the clinical application of this approach.